2023
DOI: 10.3390/plants12081632
|View full text |Cite
|
Sign up to set email alerts
|

Water Stress and Seed Color Interacting to Impact Seed and Oil Yield, Protein, Mucilage, and Secoisolariciresinol Diglucoside Content in Cultivated Flax (Linum usitatissimum L.)

Abstract: Flaxseed (Linum usitatissimum L.) is a plant with a wide range of medicinal, health, nutritional, and industrial uses. This study assessed the genetic potential of yellow and brown seeds in thirty F4 families under different water conditions concerning seed yield, oil, protein, fiber, mucilage, and lignans content. Water stress negatively affected seed and oil yield, while it positively affected mucilage, protein, lignans, and fiber content. The total mean comparison showed that under normal moisture condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 51 publications
0
5
0
1
Order By: Relevance
“…Research shows that under water-limited conditions and elevated CO 2 concentrations, plants often increase the synthesis and accumulation of secondary metabolites, such as phenolics, flavonoids, and terpenoids. These compounds act as antioxidants, scavenging ROS and protecting cellular components from oxidative damage, so increased levels of secondary metabolites contribute to enhanced water stress tolerance in barley by mitigating oxidative stress and maintaining cellular homeostasis [41,42]. In addition, the two-row barley genotypes (Behrokh and M9316) had higher grain yield, biomass, and secondary metabolites such as proline, POX, and APX antioxidants under water stress conditions and elevated CO 2 concentration.…”
Section: Discussionmentioning
confidence: 99%
“…Research shows that under water-limited conditions and elevated CO 2 concentrations, plants often increase the synthesis and accumulation of secondary metabolites, such as phenolics, flavonoids, and terpenoids. These compounds act as antioxidants, scavenging ROS and protecting cellular components from oxidative damage, so increased levels of secondary metabolites contribute to enhanced water stress tolerance in barley by mitigating oxidative stress and maintaining cellular homeostasis [41,42]. In addition, the two-row barley genotypes (Behrokh and M9316) had higher grain yield, biomass, and secondary metabolites such as proline, POX, and APX antioxidants under water stress conditions and elevated CO 2 concentration.…”
Section: Discussionmentioning
confidence: 99%
“…This difference may be attributed to variations in the ecological conditions during seed growth and storage duration. In previous studies, the values of resveratrol were reported to be, respectively, 5.72 mg/100 g and 25.66 mg/100 g [1,40]. Of the major compounds, hydroxybenzoic acid was previously reported as 4.24% in one study [31] and as 0.84 mg g −1 in another [41].…”
Section: Individual Phenolic Compoundsmentioning
confidence: 92%
“…The primary phenolic compounds found in flax seeds, namely 4-hydroxybenzoic acid, quercetin, rutin, resveratrol, and catechin hydrate, have been identified. Previous research [1] shows that resveratrol 5.72 mg/100 g, cinnamic acid 1.87 mg/100 g, and rutin 10.90 mg/100 g are the main phenolic compounds they obtained in their study with the Atalanta variety among five flaxseed varieties. In this context, when compared to our Atalanta variety, these values were found to be 2.24 µg/L for resveratrol, 12.52 µg/L for cinnamic acid, and 1.86 µg/L for rutin, which were lower than previous studies.…”
Section: Individual Phenolic Compoundsmentioning
confidence: 94%
See 1 more Smart Citation
“…Гены s1, YSED1, ysed2 и rs1 контролируют жёлтосемянность и являются важными для создания сортов льна пищевого назначения. Это делает полученные на их основе линии л-1 (гк-448 s1 × гк-210), л-2 (гк-210 × гк-448 s1), гк-554 -л-1 (гк-210 × гк-392 s1), гк-555 -л-2 (гк-210 × гк-392 s1), л-2 (гк-255 rs1 × гк-210), л-4 (гк-255 rs1 × гк-210), л-1 (гк-255 rs1 × гк-210), л-1 (гк-210 × гк-173 ysed2), л-1 (гк-136 s1 × гк-473), л-1 (гк-473 × гк-391 s1), л-1 (гк-473 × гк-255 rs1) востребованными для целей селекции, так как ранее было показано, что у жёлтосемянных образцов по сравнению с коричневосемянными выше содержание масла, слизи, фитоэстрогенов, условно незаменимых аминокислот (аргинина, гистидина) (Zare et al, 2023).…”
Section: биотехнология и селекция растенийunclassified